Incidence of ocular conditions associated with perfluoroalkyl substances exposure: Isomers of C8 Health Project in China. (April 2020) - Zeeshan, Mohammed; Yang, Yunqing; Zhou, Yang; Huang, Wenzhong; Wang, Zhibin; Zeng, Xiao-Yun; Liu, Ru-Qing; Yang, Bo-Yi; Hu, Li-Wen; Zeng, Xiao-Wen; Sun, Xiao; Yu, Yunjiang; et al.
Highlights: A large population-based study was conducted in China to assess associations between PFASs exposure and eye diseases. Exposure to PFASs especially isomers of PFOS and PFOA increases the odds of visual impairment. Vitreous disorder was adversely associated with long-chain PFASs exposure. Abstract: The detrimental effects of perfluoroalkyl substances (PFASs) on several physiological systems have been reported, but the association of PFASs with eye, one of the most sensitive and exposed organ, has never been explored. To investigate the association between eye diseases including visual impairment (VI) and PFASs isomers, a cross-sectional stratified study was conducted in 1202 Chinese population, aged 22–96 years, from Shenyang, China. A standard protocol including Snellen vision chart, slit-lamp microscopy and direct ophthalmoscopy was used to examine eye diseases/conditions relating to anterior and posterior segment of eyes. In addition, we measured the blood concentrations of 19 linear and branched PFASs at one-time point. Results indicated that blood levels of PFASs were significantly higher in eye disease group than normal group. PFASs exposure were positively associated with both combined eye diseases and individual eye diseases. Among other PFASs, linear perfluorooctane sulfonate (n-PFOS; odds ratio [OR] = 3.37, 95% confidence interval [CI]: 2.50, 4.56), branched perfluorooctane sulfonate (Br-PFOS; OR = 2.25, 95% CI: 1.72, 2.93) and linear perfluorooctanoic acid (n-PFOA; OR = 1.79, 95% CI: 1.36, 2.37) significantly increases the odds of VI. Vitreous disorder was adversely associated with long-chain PFASs exposure. For example, perfluorotridecanoic acid (PFTrDA; OR = 1.86, 95% CI: 1.51, 2.29) and perfluorodecanoic acid (PFDA; OR = 1.79, 95% CI: 1.36, 2.36) showed the most significant association. In conclusion, this study suggests higher serum PFASs levels were associated with increase odds of VI and vitreous disorder in Chinese adults.